Talaromycosis (Penicilliosis) in a Cynomolgus Macaque. Issue 4 (July 2018) - Iverson, William O.; Karanth, Subramanya; Wilcox, Angela; Pham, Cau D.; Lockhart, Shawn R.; Nicholson, Simone M.
A sexually mature Chinese-origin female Macaca fascicularis assigned to the high-dose group in a 26-week toxicology study with an experimental immunomodulatory therapeutic antibody (a CD40 L antagonist fusion protein) was euthanized at the scheduled terminal sacrifice on study day 192. The animal was healthy at study initiation and remained clinically normal throughout the study. On study day 141, abnormal clinical pathology changes were found during a scheduled evaluation; splenomegaly was detected on study day 149 and supported by ultrasound examination. At the scheduled necropsy, there was marked splenomegaly with a nodular and discolored appearance. Cytologic examination of a splenic impression smear revealed yeast-like organisms within macrophages. Histologically, there was disseminated systemic granulomatous inflammation with 2- to 3-μm oval, intracytoplasmic yeast-like organisms in multiple organs identified as Talaromyces (Penicillium) marneffei . This organism, not previously reported as a pathogen in macaques, causes an important opportunistic infection in immunosuppressed humans in specific global geographic locations.